PENGARUH KEPEMIMPINAN, EFIKASI DIRI, DAN KETERLIBATAN KERJA TERHADAP KOMITMEN PROFESI GURU SMA NEGERI DI KABUPATEN SIAK PROVINSI RIAU - Tasril, Tasril -; Akbar, Maruf; Saam, Zulfan (Journal of Education Research in Administration and Management (JERAM), 2017)
The purpose of this study is to study the influence of leadership, self-efficacy, and work engagement on high school teachers’ professional commitment at Siak Regency of Riau Province. This research uses the quantitative approach with the survey method. The population in this study were 96 high school teachers in Siak Regency of Riau Province. The results of this study indicate that; (1) There is a direct positive influence of leadership on high school teachers’ professional commitment. (2) There is a direct positive influence of self-efficacy on high school teachers’ professional commitment. (3) There is a direct positive influence of work engagement on high school teachers’ professional commitment. (4) There is a direct positive influence of leadership on self-efficacy. 5) There is a  direct positive influence of leadership on work engagement. (6) There is a direct positive influence of self-efficacy on work engagement.  Thus, the improvement of high school teachers’ professional commitment can be achieved well if there is strong influence from leadership, self-efficacy, and work engagemen which are well built. Keywords: leadership, self-efficacy, work engagement, professional commitment.